2003
DOI: 10.1080/10473220390237539
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Evidence on the Carcinogenicity of Metalworking Fluids

Abstract: The purpose of this review is to organize and evaluate the epidemiologic evidence regarding the potential carcinogenicity of metalworking fluids. Published literature was initially examined to identify the key contributions, with a strong emphasis on the series of studies by Eisen et al. A key challenge to addressing the issue is the diversity of metalworking fluids, additives, and by-products produced in use, along with the notable changes in the composition and use of such agents over time. Although several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…Insofar as the galvanizing sector is concerned, it is one of the main industrial activities that releases dioxins to air , recognized by the IARC as carcinogens in humans (IARC, 2012) and related to increased risk of leukemias in general population (Consonni et al, 2008), a finding that could be related to the excess risk observed by us in the environs of this industrial group. Another noteworthy result is the excess risk found in the environs of installations for the surface treatment of metals and plastic, a group of metal industries that use mineral oils and metalworking fluids, a range of oils and other chemicals substances known to be carcinogens in humans (Savitz, 2003). In this connection, an Italian study detected increased risk of childhood leukemia related to paternal exposure to mineral oils (Miligi et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…Insofar as the galvanizing sector is concerned, it is one of the main industrial activities that releases dioxins to air , recognized by the IARC as carcinogens in humans (IARC, 2012) and related to increased risk of leukemias in general population (Consonni et al, 2008), a finding that could be related to the excess risk observed by us in the environs of this industrial group. Another noteworthy result is the excess risk found in the environs of installations for the surface treatment of metals and plastic, a group of metal industries that use mineral oils and metalworking fluids, a range of oils and other chemicals substances known to be carcinogens in humans (Savitz, 2003). In this connection, an Italian study detected increased risk of childhood leukemia related to paternal exposure to mineral oils (Miligi et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…While this study was an important advancement in research on MWFs, it was not possible to control for smoking. In addition, the exposure settings were limited to three large auto manufacturing plants in Michigan,34 leaving unanswered questions about MWF exposure in other settings, including small machine shops that are prevalent throughout the world.…”
mentioning
confidence: 99%
“…Several publications confirmed a possible carcinogenic potential of metalworking fluids (MWF) [Mirer et al, 1988;Park, 2001;Savitz, 2003;Agalliu et al, 2005;Bardin et al, 2005;Malloy et al, 2007], but an explicit association with testicular cancer has never been described before. MWF are a complex mixture of chemicals and toxic microbial agents [Gordon, 2004].…”
Section: Discussionmentioning
confidence: 94%